2021
DOI: 10.1101/2021.07.06.21260086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proxalutamide (GT0918) Reduces the Rate of Hospitalization in mild-to-moderate COVID-19 Female Patients: A Randomized Double-Blinded Placebo-Controlled Two-Arm Parallel Trial

Abstract: BackgroundAntiandrogens were shown to be effective in mild-tomoderate COVID-19 male patients, supported by the SARS-CoV-2 dependency on transmembrane protease, serine 2 (TMPRSS2), which is solely modulated by androgens, for cell entry. While women with hyperandrogenism experiment more symptoms in COVID-19 compared to women without hyperandrogenism, and the chronic use of an antiandrogen seemed to mitigate these symptoms, whether the benefits would be observed in overall females is unknown. The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…In accordance with our hypothesis, in both studies, substantial reductions in hospitalization rates were observed, 24,25 supported by the previously reported antiviral and protective radiological effects of proxalutamide. 26,27 We aimed to evaluate whether the improvements in clinical outcomes observed with the use of proxalutamide is accompanied by biochemical improvements in terms of inflammatory and thromboembolic parameters, since these are two cornerstones of the SARS-CoV-2 pathophysiology, demonstrated to be important surrogate markers of COVID-19 infections playing as independent prognostic factors.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…In accordance with our hypothesis, in both studies, substantial reductions in hospitalization rates were observed, 24,25 supported by the previously reported antiviral and protective radiological effects of proxalutamide. 26,27 We aimed to evaluate whether the improvements in clinical outcomes observed with the use of proxalutamide is accompanied by biochemical improvements in terms of inflammatory and thromboembolic parameters, since these are two cornerstones of the SARS-CoV-2 pathophysiology, demonstrated to be important surrogate markers of COVID-19 infections playing as independent prognostic factors.…”
Section: Introductionsupporting
confidence: 92%
“…All missing data are Missing Completely at Random (MCAR), except for six male patients that dropped out, although their outcomes were known and counted for intention-to-treat (ITT) analysis for hospitalization rate elsewhere. 24,25 The amount of missing data was provided for each parameter at each time. However, treatment effect for hospitalization rate was calculated adjusted for missing data, without significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings support the hypothesis that anti-androgens could be effective against COVID-19 with observational and RCTs in early COVID-19 have demonstrated that dutasteride, spironolactone and proxalutamide could protect against COVID-19 disease progression [ 190 - 195 ]. These benefits have also been observed in hospitalized patients through RCTs for finasteride and proxalutamide [ 191 , 193 , 194 , 196 , 197 ]. Thus, the strong biological plausibility of androgen-dependent mechanisms of SARS-CoV-2 cell invasion, the multiple corresponding epidemiological observations in both excess and blockage of androgen activity, observational, and several RCTs demonstrating the efficacy of a variety of anti-androgens in preventing COVID-19 disease progression support the recommendation for their use during hospitalization.…”
Section: Anti-androgen Therapy and Covid-19mentioning
confidence: 85%